The interaction of supernova 2018evt with a substantial amount of circumstellar matter – An SN 1997cy-like event. Issue 2 (28th November 2022) - Yang, Yi; Baade, Dietrich; Hoeflich, Peter; Wang, Lifan; Cikota, Aleksandar; Chen, Ting-Wan; Burke, Jamison; Hiramatsu, Daichi; Pellegrino, Craig; Howell, D Andrew; McCully, Curtis; Valenti, Stefano; et al.
ABSTRACT: A rare class of supernovae (SNe) is characterized by strong interaction between the ejecta and several solar masses of circumstellar matter (CSM) as evidenced by strong Balmer-line emission. Within the first few weeks after the explosion, they may display spectral features similar to overluminous Type Ia SNe, while at later phase their observation properties exhibit remarkable similarities with some extreme case of Type IIn SNe that show strong Balmer lines years after the explosion. We present polarimetric observations of SN 2018evt obtained by the ESO Very Large Telescope from 172 to 219 d after the estimated time of peak luminosity to study the geometry of the CSM. The non-zero continuum polarization decreases over time, suggesting that the mass-loss of the progenitor star is aspherical. The prominent H α emission can be decomposed into a broad, time-evolving component and an intermediate-width, static component. The former shows polarized signals, and it is likely to arise from a cold dense shell (CDS) within the region between the forward and reverse shocks. The latter is significantly unpolarized, and it is likely to arise from shocked, fragmented gas clouds in the H-rich CSM. We infer that SN 2018evt exploded inside a massive and aspherical circumstellar cloud. The symmetry axes of the CSM and the SN appear to be similar. SN 2018evt shows observational properties common to events that display strong interaction between the ejecta and CSM, implying that they share similar circumstellar configurations. Our preliminary estimate also suggests that the circumstellar environment of SN 2018evt has been significantly enriched at a rate of ∼0.1 M⊙ yr −1 over a period of >100 yr.